(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper advances an author’s concept of an in-situ monolithic pavement produced by thermal melting of natural rock followed by controlled cooling. A process flow is outlined (subgrade preparation—high-temperature heating—melt leveling—gradient cooling), along with rock-selection criteria and pre-project testing. Engineering constraints, HS&E aspects, and a pilot validation program for mountainous regions are discussed.